Teaching Scholarly Writing to Doctoral Students: Giving Novice Scholars a Running Start - Bruce Barnett; Rosemary Caffarella; Michael Gimmestad University of Northern Colorado (Adult Education Research Conference, 1998)
Students entering doctoral programs in adult education and related fields often experience culture shock. Perhaps the biggest adjustment is learning how to think and write like a scholar. This paper examines how involvement by doctoral students in a formal scholarly writing project during their first semester of study influenced their subsequent doctoral experience and professional work.